113k views
4 votes
Instructions: Write the explicit rule. Remember to simplify and do not put spaces in your answer. Sequence: 30,0,−30,−60,… 30 , 0 , − 30 , − 60 , … = a n = Answer

1 Answer

4 votes

Answer:

a(n)=60-30n

Explanation:

Equation to use:

a(n) = a(1) + d(n-1)

where a(1) is the first term, d is the common difference between terms, and n is the nth term you are trying to find.

In this case, a(1) is 30, d is -30, and n is just n.

If you plug that into the equation and use the distributive property, you would get: a(n) = 30 -30n + 30.

Adding the two 30's gets you: a(n) = 60 - 30n, which is the solution.

User Stanley Ulili
by
5.1k points